2020
DOI: 10.1007/s10557-020-07083-w
|View full text |Cite
|
Sign up to set email alerts
|

Novel Anti-inflammatory Effects of Canagliflozin Involving Hexokinase II in Lipopolysaccharide-Stimulated Human Coronary Artery Endothelial Cells

Abstract: Purpose Vascular inflammation and disturbed metabolism are observed in heart failure and type 2 diabetes mellitus. Glycolytic enzyme hexokinase II (HKII) is upregulated by inflammation. We hypothesized that SGLT2 inhibitors Canagliflozin (Cana), Empagliflozin (Empa) or Dapagliflozin (Dapa) reduces inflammation via HKII in endothelial cells, and that HKII-dependent inflammation is determined by ERK1/2, NF-κB. and/or AMPK activity in lipopolysaccharide (LPS)-stimulated human coronary artery endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 56 publications
2
33
1
Order By: Relevance
“…In vivo and in vitro studies have shown that pathological mechanical forces stimulate cytokine production and expression of adhesion molecules, leading to stiffness of vessels and monocyte adhesion [ 17 , 44 ]. Interestingly, none of the three SGLT-2i’s inhibited stretch-induced interleukin secretion ( Figure 5 ), which is in contrast to previous data showing that SGLT-2i’s inhibit interleukin production of endothelial cells from humans, as well as from ApoE (-/-) mice [ 45 , 46 ]. One potential explanation might be that the stretch-induced interleukin secretion of HCAECs is much milder than that caused by lipopolysaccharide (1.5–2 fold vs. 6–7 fold) [ 46 ], making it a less optimal model to investigate the potential anti-inflammatory effects of SGLT-2i’s.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…In vivo and in vitro studies have shown that pathological mechanical forces stimulate cytokine production and expression of adhesion molecules, leading to stiffness of vessels and monocyte adhesion [ 17 , 44 ]. Interestingly, none of the three SGLT-2i’s inhibited stretch-induced interleukin secretion ( Figure 5 ), which is in contrast to previous data showing that SGLT-2i’s inhibit interleukin production of endothelial cells from humans, as well as from ApoE (-/-) mice [ 45 , 46 ]. One potential explanation might be that the stretch-induced interleukin secretion of HCAECs is much milder than that caused by lipopolysaccharide (1.5–2 fold vs. 6–7 fold) [ 46 ], making it a less optimal model to investigate the potential anti-inflammatory effects of SGLT-2i’s.…”
Section: Discussioncontrasting
confidence: 97%
“…However, the involvement of AMPK phosphorylation is still under discussion. In the previous studies of Uthman et al, AMPK activation was not observed in EMPA or DAPA, but only in CANA treated cells [ 46 ].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…According to other study groups [57], canagliflzoin reduced proinflammatory cytokines by lowering hexose kinase II (HKII) and blocking ERK phosphorylation, but not affecting NF-κB in LPS-stimulated human coronary artery endothelial cells (HCAECs). Dapagliflozin also suppressed iNOS, TNF-α, IL-1β, and IL-6 mRNA expression by attenuating the NF-κB transcription factor in dietinduced atherosclerosis in rat aortic arteries [58].…”
Section: Discussionmentioning
confidence: 95%
“…The HCAECs were seeded in each well of a 12-well culture plate at a density of 5x104 cells and incubated for 18 h at 37˚C in 5% CO 2 and 95% humidified air. The HCAECs were then subjected to 1 µg/ml lipopolysaccharide (LPS; Merck KGaA) challenge for 3 h (22). Subsequently, the HCAECs were treated with IVIGs (25 mg/ml) (Tonrol Bio-pharmaceutical Co., Ltd.) and vehicle for 18 h (23).…”
Section: Identification Of Degsmentioning
confidence: 99%